Disposition of asciminib, a potent BCR-ABL1 tyrosine kinase inhibitor, in healthy male subjects - Tran, Phi; Hanna, Imad; Eggimann, Fabian Kurt; Schoepfer, Joseph; Ray, Tapan; Zhu, Bing; Wang, Lai; Priess, Petra; Tian, Xianbin; Hourcade-Potelleret, Florence; Einolf, Heidi J. (Xenobiotica, 2020)
Asciminib is a potent, specific BCR-ABL1 inhibitor being developed for the treatment of patients with chronic myelogenous leukemia (CML) and Philadelphia chromosome positive acute lymphoblastic leukemia (Ph + ALL). Here, we present the results of human oral absorption, distribution, metabolism, excretion (ADME) and in vitro studies that together provide an overall understanding of the metabolism, distribution and clearance of asciminib in humans. Asciminib was rapidly absorbed with a maximum plasma concentration at two hours post-dose. Total radioactivity and asciminib showed similar terminal half-lives in plasma. Oral asciminib absorption ranged between a minimum of 33%, and a maximum of 57% based on the metabolite profiles of late time-point feces collections. Asciminib was eliminated mainly through feces via unchanged asciminib excretion and metabolism. Direct glucuronidation and oxidation were major metabolic pathways in human that were catalyzed predominantly by UDP-glucuronosyltransferase (UGT)2B7 and cytochrome P450 (CYP)3A4, respectively. The relative contribution of the glucuronidation pathway to the total clearance of asciminib via metabolism is estimated to range ∼28-58%, whereas the relative contribution of the oxidative pathway is estimated to range ∼37-64%, based upon the maximum oral absorption in humans.